The Miracle of Large Numbers. - BOKLIN, ALEX (Skeptic, 2014)
The article discusses how to explain miraculous events through application of the law of large numbers and understanding of probabilities. Topics include the rational theory of coincidences, extrasensory perception (ESP), and arguments from cosmological design. Also discussed are arguments from design in biological systems, and journalist and author Michael Drosnin's analysis of the Bible code.